Encapsulating Mo-Doped TiO2 Anatase in N-Doped Amorphous Carbon With Excellent Lithium Storage Performances - Xia, Ying; Rong, Chao; Yang, Xiaoyan; Lu, Fengqi; Kuang, Xiaojun (Frontiers in Materials, 2019)
For improving the capability, cycling stability and rate capacity of anatase TiO2-based electrode, Mo-doped TiO2 anatase encapsulated in nitrogen-doped amorphous carbon (denoted for Mo-TiO2@NC) were synthesized through a facile hydrothermal method and followed by coating with polyaniline (PANI) and heating treatment. When tested as anode for lithium ion batteries, the Mo-TiO2@NC electrode showed initial discharge and charge capacities of 850.7 and 548.3 mAh g-1 at a current density of 85 mA g-1, respectively, with a remarkable discharge capacity maintained at 449.2 mAh g-1 after 100 cycles. Even at high current density of 850 mA g-1, a reversible capacity of 154 mAh g-1 after 200 cycles is obtained, displaying good rate capacity and long-term cycling stability. The outstanding electrochemical performance of Mo-TiO2@NC could be attributed to the synergistic effect of aliovalent ions doping and carbon coating.